1971
DOI: 10.1097/00004032-197108000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Dosimetry of Internal Contamination by Inorganic Compounds of Cobalt

Abstract: The whole body retention of cobalt during a period of 400 days after injection of CoCl, has been determined for a strain of specific-pathogen-free albino rats. The method used to fit both exponential and power functions to the data and the application of statistical tests which justify the selection of a function with five exponential terms as the best fit are dcscribed. The statistical mcthods used in this paper are presentcd in detail because of their possible application to other studics of a similar nature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

1975
1975
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…Hollins and McCullough [16] reported that at 10 72 h post intraperitoneal administration of radiolabelled cobalt chloride, the liver, skeleton and muscle contained 20 25% of total body activity with 7 8% accumulating in the kidney. Hollins and McCullough [16] reported that at 10 72 h post intraperitoneal administration of radiolabelled cobalt chloride, the liver, skeleton and muscle contained 20 25% of total body activity with 7 8% accumulating in the kidney.…”
Section: Discussionmentioning
confidence: 99%
“…Hollins and McCullough [16] reported that at 10 72 h post intraperitoneal administration of radiolabelled cobalt chloride, the liver, skeleton and muscle contained 20 25% of total body activity with 7 8% accumulating in the kidney. Hollins and McCullough [16] reported that at 10 72 h post intraperitoneal administration of radiolabelled cobalt chloride, the liver, skeleton and muscle contained 20 25% of total body activity with 7 8% accumulating in the kidney.…”
Section: Discussionmentioning
confidence: 99%
“…Following the intravenous administration of 1 mg Co(II)/kg as cobaltous chloride to rats, 4.7% of the dose was secreted in the bile by 2 h (Gregus & Klaassen, 1986). Following the injection of the same dose of Co(II) to rats, 72.6% of the dose was excreted in the urine by 4 d. Cobalt was distributed to the largest extent to the liver, kidneys, and heart following the oral or parental administration of soluble cobalt to the rat (Hollins & McCullough, 1971;Stenberg, 1983;Alexanderson, 1988) or following the oral or intravenous administration of cobaltous chloride to rabbits, swine, and calves (Gregus & Klaassen, 1986). These results suggested that there was no species variability.…”
mentioning
confidence: 99%
“…Therefore, there may be a longer component to the blood concentration curve that was not determined in this study. Hollins and McCullough (1971) were able to describe cobalt whole-body retention in rats by a sum of five exponential terms over a period of 400 d. They used radioactive cobalt and probably observed cobalt exchange into endogenous compounds that have a very slow turnover. Because the amounts of cobalt in the extra two exponential terms were so small, they probably have little toxicological significance.…”
mentioning
confidence: 99%
“…Testes data in the literature were sparse. Based on our assumed interpretation of the data of Hollins and McCullough (1971) and that of Gregus and Klaassen (1986), approximately 0.2% ID remained in testes at 2 hr and 0.4% ID of the activity remaining in the carcass remained in testes at 10 d. No literature values could be found for 60 Co in ovaries.…”
Section: Resultsmentioning
confidence: 82%